HUBUNGAN PERAN PERAWAT TERHADAP PENCEGAHAN DAN PENGENDALIAN INFEKSI - Noor, Sirajudin; Hutahaean, Serri; Nababan, Dosmaida (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Prevention of infections in hospitals is very important to do, given the high incidence of infections in hospitals. This is an important note considering that this infection can happen to anyone, be it patients, nurses, doctors, employees, and so on. The role of the health team, especially nurses, needs to be involved in reducing the number of infections in the hospital. The purpose of this study was to determine the relationship between the nurse's role and infection prevention and control in the hospital. This research was conducted in June 2023 at a Tangerang Hospital. This type of research is a quantitative analytic descriptive design with a cross-sectional approach. Sampling is a total sampling of 100 respondents. The instrument in this study was to use a questionnaire. Data were analyzed using the Chi-Square Test. The results of the study obtained a p-value <0.05 (0.006) meaning that there is a significant relationship between the role of nurses in infection prevention and control. This study shows that nurses have played a good role in preventing and controlling infection, so it can be concluded that nurses who play a good role, better the infection prevention and control efforts. The recommendation from this study is the need for action from hospital management to improve the quality of the role of nurses by providing motivational support or rewards so that infection prevention and control efforts can be maximized.